Long spine fusions to the sacrum-pelvis are associated with greater post-operative proximal junctional kyphosis angle in sitting position - Cecchinato, Riccardo; Berjano, Pedro; Compagnone, Domenico; Langella, Francesco; Nervi, Andrea; Pezzi, Andrea; Mangiavini, Laura; Lamartina, Claudio (European spine journal, 2022)
Study design A single-centre retrospective study. Background and Purpose Although adult patients spend most of their time in sitting positions, the assessment of spinopelvic parameters in adult deformity surgery is commonly performed in standing X-rays. Our study compares the standing and sitting sagittal alignment parameters in subjects who underwent thoracolumbar fusion. Methods Patients who underwent corrective surgery for adult scoliosis with at least five instrumented vertebra were stratified according to the upper instrumented vertebra (UIV) and pelvic fixation. Group A:UIV proximal to T6 with pelvis fixation. B:UIV lower than T6 and pelvic fixation. Group C: thoracolumbar fusion without pelvic fixation. Post-operative spinopelvic sagittal parameters were measured in both standing and sitting X-rays. Results A total of 51 patients were enrolled in the study (11:Males and 40:Females). The mean age was 52.3 ± 21.7y/o. The comparison of post-operative standing and sitting X-ray within the group A and B showed that a significant change was observed in terms of JA-Junctional Angle-(Group A 6.3 ± 4.3 vs. 8.1 ± 3.3, p value = 0.03) (Group B 8.5 ± 6.4 vs. 10.9 ± 6.4, p value = 0.02). Group C showed statistically significant difference in terms of PT (15.6 ± 11.2 vs. 19.3 ± 9.2, p value = 0.04), AVA-Acetabular Version Angle-(41.1 ± 5.9 vs. 48.3 ± 6.6, p value < 0.01) and LL (− 51.3 ± 16.0 vs. − 42.6 ± 10.7, p value < 0.01). Conclusion In our series, the post-operative sagittal alignment showed peculiar behaviours and adaptations in sitting position, depending on the length and the site of the instrumented area. If the pelvis is included, the JA tends to significantly increase in sitting position. These findings can improve the knowledge of pathologies as proximal junctional kyphosis or specific cases of anterior hip impingement. Level of evidence IV.